Clearing vs. leakage: Does note monopoly increase money and credit cycles? - Per Hortlund (Stockholm School of Economics, The Economic Research Institute (EFI), 2005)
The effects of note monopolisation on the amplitude of money and credit cycles are studied. Swedish bank data for 1871-1915 reveal that money cycles became smaller, but credit cycles larger, after the Bank of Sweden gained a note monopoly in 1904. At the same time, the money multiplier decreased, while the credit multiplier increased. If the central bank's reserve ratio is larger than that of the commercial banks, and if the currency-deposit ratio is sufficiently large, the leakage effect could dominate the loss-of-clearing effect (base expansion), such that the money multiplier decreases. That the credit multiplier simultaneously increased is attributed mainly to an increasing time-demand deposit ratio, which increased the credit capacity of the banking system.
Keywords: E32; E42; E51; 330; Clearing mechanism; Credit expansion; Currency-deposit ratio; Fiduciary money; Free banking; Leakage; Money multiplier; Verrechnungsverkehr; Geldpolitik; Geldschöpfung; Geldangebot; Free Banking; Schweden